Wall Magazine Utilization and Reading Literacy Development: A Newman Error Analysis Framework Study in Elementary Education - Ahmad Rizky; Sasmita Sari (Papanda Publisher, 2026)
This study analyzes the utilization of wall magazines as a medium to enhance students’ reading literacy skills, particularly in understanding factual and opinion-based texts, at SDN 01 Mendayun. The background of the study highlights the suboptimal use of wall magazines in schools, despite their potential to stimulate students’ interest in reading and support literacy development. Using a qualitative case study approach, the research involved ten fifth-grade students, of whom six were selected through purposive sampling to represent high, medium, and low literacy performance. Data were collected through literacy tests, interviews, and documentation, then analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal variations in students’ literacy abilities based on Newman’s indicators: reading, comprehension, and encoding. High-performing students demonstrated strong reading accuracy and the ability to distinguish factual from opinion statements, while medium-performing students showed partial understanding but struggled in articulating conclusions. Low-performing students exhibited significant challenges, particularly in comprehension and drawing conclusions. The study concludes that wall magazines play a supportive role in increasing students’ reading interest and reading accuracy, yet their effectiveness requires consistent teacher guidance, structured learning activities, and regular content updates. These findings underscore the importance of optimizing wall magazine use as an engaging literacy-learning medium in elementary schools.